2016
DOI: 10.1016/j.yexcr.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan based hydrogels provide an improved model to study megakaryocyte–matrix interactions

Abstract: Hyaluronan (HA) is a glycosamminoglican involved in cell biology as well as a relevant polymer for tissue engineering and regenerative medicine. Megakaryocytes (Mks) are immersed in a mesh of extracellular matrix (ECM) components that regulate their maturation in the bone marrow (BM) and the release of platelets into the bloodstream. While fibrous ECMs such as collagens and fibronectin have been demonstrated to differently regulate Mk function and platelet release, the role of HA, that fills the majority of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 60 publications
0
22
1
Order By: Relevance
“…50,51,56 However, MKs are distinguished from other progenitor cell types by a number of features, including the intracellular localization of HA and cognate receptors. 30,57 Despite pronounced thrombocytopenia in Hyal-2 KO animals, we found a statistically insignificant decrease in the number of MKs present within the BM when compared with controls ( Figure 1B). Our present data also reveal that maturation ( Figure 3B) and survival (Figure 2, CeE) of MKs in Hyal-2 KO animals are severely impaired.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…50,51,56 However, MKs are distinguished from other progenitor cell types by a number of features, including the intracellular localization of HA and cognate receptors. 30,57 Despite pronounced thrombocytopenia in Hyal-2 KO animals, we found a statistically insignificant decrease in the number of MKs present within the BM when compared with controls ( Figure 1B). Our present data also reveal that maturation ( Figure 3B) and survival (Figure 2, CeE) of MKs in Hyal-2 KO animals are severely impaired.…”
Section: Discussionmentioning
confidence: 73%
“…28,29 Data from our laboratory and others indicate that MKs and platelets contain HA, but little is known about its role in these cells. 30,31 In addition, we found that both mouse and human MKs and platelets contain HYAL2 mRNA and protein with no evidence for HYAL1. 31,32 Recently, it was reported that irradiated wild-type (WT) mice receiving transplants of Hyal-2 KO BM had reduced platelet levels, suggesting a role for intrinsic HA depolymerization by MKs in thrombopoiesis.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…After entry, the artery splits into multiple branches that give rise to a multitude of small thin-walled arterioles and sinusoids that let cells to enter the bloodstream [46]. The main bone marrow scaffolding is represented by the components of the extracellular matrix (ECM), which provide, depending on their composition, localization and stiffness, the ideal microenvironment to support hematopoietic stem cell (HSC) differentiation into committed lineages and release of mature cells into blood [79]. …”
Section: Introductionmentioning
confidence: 99%
“…One of the major challenges for the field is the development of bio-compatible scaffolds that can meet the needs to support platelet formation and functions ex vivo [911]. To this regard, silk fibroin is a biologically-derived protein polymer purified from domesticated silkworm ( Bombyx mori ) cocoons that has demonstrated excellent properties for biomedical applications, including biocompatibility, robust mechanical strength, and slow, controlled degradation to nontoxic products in vivo [1214].…”
Section: Introductionmentioning
confidence: 99%